2019
DOI: 10.1103/physrevd.100.015003
|View full text |Cite
|
Sign up to set email alerts
|

Rare top decays as probes of flavorful Higgs bosons

Abstract: We study a version of Two Higgs Doublet Models with non-standard flavor violation in the up quark sector. We find branching ratios for the rare top decays t → hc and t → hu that are within reach of current and future colliders, while other flavor constraints from rare B decays and neutral D meson mixing, as well as constraints from Higgs signal strength measurements remain under control. The most prominent collider signature of the considered setup is pp → tH → ttc, providing continued motivation to search for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 106 publications
0
10
0
Order By: Relevance
“…Similar expressions hold of course for second generation quarks. The sensitivity of measurements at colliders is expected to be similar in both cases, just as in other flavourviolating top decays [33][34][35][36][37][38].…”
Section: Top Decaysmentioning
confidence: 83%
“…Similar expressions hold of course for second generation quarks. The sensitivity of measurements at colliders is expected to be similar in both cases, just as in other flavourviolating top decays [33][34][35][36][37][38].…”
Section: Top Decaysmentioning
confidence: 83%
“…There are several possible future directions to further explore the FSSM. The rank-1 ansatz for the Yukawa couplings has been successfully implemented in the quark sector in non-supersymmetric versions of the model [5,11,[112][113][114]. It has been shown that in the considered scenarios quark flavor changing neutral currents can be relatively easily in agreement with experimental bounds.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible future directions to further explore the FSSM. The rank-1 ansatz for the Yukawa couplings has been successfully implemented in the quark sector in non-supersymmetric versions of the model [5,11,[70][71][72]. It has been shown that in the considered scenarios quark flavor changing neutral currents can be relatively easily in agreement with experimental bounds.…”
Section: Discussionmentioning
confidence: 99%